"Passing" and its effects on Brazilian transgender people's sense of belonging to society: A theoretical study. (11th May 2021) - Dias, Cristiana Kaipper; da Rocha, Leonardo Rafael Leite; Tateo, Luca; Marsico, Giuseppina
Abstract: Passing is the research of oneself by trying to look and to be seen as a member of a social group by assuming its features. Individuals performing this process are willing to undergo several physical and behavioural changes to achieve this aspiration. Passing generally occurs among members of minority groups suffering discrimination who want to diminish the psycho‐social discomfort of their experience. Examples of passing are the attempts by ethnic minorities to whiten their skin, or the efforts of transgender people to look as much as possible, in the eyes of others, like the gender with which they identify. This paper aims to discuss aspects related to trans people's pursuit of passing, taking the Theory of Performativity of Gender and the Cultural Semiotic Psychology as its theoretical basis. This is a theoretical‐reflexive study that will debate the topic based on studies of this topic in Brazilian society.